1987
DOI: 10.1080/01688170.1987.10510288
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the Juxtaganglionar Organ, a Putative Endocrine Gland Associated with the Cerebral Ganglia ofAplysia juliana

Abstract: Electron microscopy was used to examine the morphology of a putative endocrine gland, thejuxtaganglionar organ (JO), and its relation to the cerebral ganglia of the hermaphroditic opisthobranch gastropod Aplysia juliana. The JO is a well-vascularized, poorly innervated tissue of glandular cells-rich in mitochondria, lipids, ribosomes, and endoplasmic reticulum, with sparse cilia and membrane-limited secretory granules -within the connective tissue sheath just exterior to the neuronal soma in the dorsal and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Physiological characteristics of dorsal bodies suggest that these glands are inactive in virgin snails, are activated by mating, and remain active during the reproductive phase of the organisms (Joosse and Geraerts 1983;Khan et al 1990;Saleuddin et al 1997). Ultrastructural analyses have suggested that the juxtaganglionar organ of prosobranch snails may be analogous to the dorsal bodies (Switzer-Dunlap 1987).…”
Section: Hormonal Control Of Sexual Differentiation and Reproduction mentioning
confidence: 97%
“…Physiological characteristics of dorsal bodies suggest that these glands are inactive in virgin snails, are activated by mating, and remain active during the reproductive phase of the organisms (Joosse and Geraerts 1983;Khan et al 1990;Saleuddin et al 1997). Ultrastructural analyses have suggested that the juxtaganglionar organ of prosobranch snails may be analogous to the dorsal bodies (Switzer-Dunlap 1987).…”
Section: Hormonal Control Of Sexual Differentiation and Reproduction mentioning
confidence: 97%
“…Such organs were first reported in acochlidian species for the hermaphroditic Hedylopsis ballantinei and H. spiculifera by Sommerfeldt and Schrödl (2005). While Huber (1993) regarded dorsal bodies as an autapomorphy of pulmonates, similar structures called "juxtaganglionar organ" were additionally found in aplysiid opisthobranchs, especially during the period of female gonad development, in the gymnosome Hydromeles, and in both sexes of a number of gonochoric prosobranchs (Martoja, 1965a,b;Switzer-Dunlap, 1987). Based on the ultrastructural and neurosecretory function of female gonadotropic factors, dorsal bodies and juxtaganglionar organs were considered homologous by Switzer-Dunlap (1987).…”
Section: Nervous Systemmentioning
confidence: 97%
“…Identical organs have been described from basommatomorphan pulmonates (see Switzer-Dunlap, 1987) and are commonly regarded as an autapomorphy for pulmonates (see Huber, 1993). However, their presence seems plesiomorphic not only for euthyneurans; similar, but less concentrated neurosecretory tissues associated with the cerebral ganglia ('juxtaganglionar organ') have also been detected in aplysiid opisthobranchs, the gymnosome Hydromeles, and several prosobranchs such as Patella, Trochocochlea, Diodora and Haliotis, especially during the period of female gonad maturation (Martoja, 1965a, b;Switzer-Dunlap, 1987). Careful studies will ultimately reveal dorsal bodies to be present in other acochlidian species and other opisthobranch groups as well, and their special structure and functions might have some phylogenetic significance.…”
Section: Morphologymentioning
confidence: 99%